Elevated dust deposition in Tierra del Fuego (Chile) resulting from Neoglacial Darwin Cordillera glacier fluctuations - Vanneste, Heleen (2016)
Atmospheric mineral dust is intrinsically linked with climate. Although dust flux variability on glacial–interglacial timescales is well documented, Holocene dust records remain scarce. To fill this gap, we conducted elemental, isotopic and sedimentological analyses on a peat core from the Karukinka Natural Park in Tierra del Fuego. An 8000-year-old mineral dust record was extracted indicating three periods of elevated dust deposition: (i) 8.1–7.4 cal ka BP, (ii) 4.2 cal ka BP and (iii) 2.4–1.4 cal ka BP. The two oldest peaks are related to volcanic eruptions of the Hudson and Monte Burney volcanoes, respectively. The most recent dust peak, however, has a rare earth element and neodymium isotopic composition that resembles the geochemical signature of outwash plain sediments from the Darwin Cordillera. Since the timing of this dust peak corresponds to a period of glacier retreat between Neoglacial advances III and IV, we infer that Holocene aeolian dust fluxes in southern Patagonia are mostly driven by glacial sediment availability. Our results underline the important role of glaciers in producing aeolian dust in high-latitude regions, and they imply that the current retreat of glaciers worldwide may result in elevated atmospheric dust loads.